A leitura em LE/Inglês e a leitura escolar: uma prática co-construída por professores e alunos - Lazarotto, Carmen Ângela (Universidade do Vale do Rio do Sinos, 2006)
This study investigates how the reading classes in English are related to the reading work developed at a public school in a city in the western region of the state of Santa Catarina. The data generation is composed of participant observation of the English classes as well as of the other reading classes, which were scheduled following a weekly rotating scheme. The data triangulation was done based on the analysis of the field notes, documents, questionnaire, interviews with teachers and students, audiovisual recordings of the school reading classes and participative class council. The investigation employed a qualitative approach, which focused on the relation between the English reading classes and the school reading classes considering that both of them should be significant and co-constructed by the participants involved in the teaching learning process. The results indicate that there is a distance between the teachers’ normative discourse and their social actions and that both, teachers and students, co
Keywords: alfabetização; aprendizagem; ensino; leitura escolar; lingua inglesa; Letras e Artes; Lingüística